PENGEMBANGAN MEDIA DIGITAL KARTU DOMINO RANTAI MAKANAN (DORAMA) PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Maria Erica Istyasiwi; Yetty Auliaty; Dudung Amir Sholeh (Program Studi PGSD Universitas Flores, 2021)
This study aims to develop the Dominoes card game media in the science learning of food chain material for class V SD in the form of an application and also to determine the feasibility of the Food Chain Dominoes card game media. The research method used is Research and Development or R&D. The research model used is ADDIE. Data collection instruments in the form of observations, interviews, expert test questionnaires and student response questionnaires. The expert test process is carried out to material experts, media experts and linguists. The results of the material expert test validation are 100% so it can be said to be